The Credibility of the United Kingdom's Commitment to the Erm : Intentions Versus Actions - Masson, Paul (IMF Working Papers; Working Paper ;, 1994)
The paper presents estimates of a model of the credibility of the U.K. commitment to its central parity against the deutsche mark during the period of U.K. ERM membership (1990-92). The measure of credibility used is the long-term interest differential with Germany. Credibility is decomposed into two aspects: an assessment of whether the government was truly committed to the ERM, and the probability that even a committed government would be able to continue to bear the unemployment costs. Doubts about the first aspect-which could lead to a self-fulfilling crisis-are shown to have declined steadily during the period of ERM membership, while the second aspect is estimated to have become increasingly important, due to rising unemployment.